Awareness of Global Citizenship among Thai youth : Political Roles in a Democratic System - Chittanont, Manassawin (Journal for Developing the Social and Community, 2024)
The research article of “Awareness of Global Citizenship among Thai youth : Political Roles in a Democratic System” aims 1) to study the factors affecting the change in citizenship awareness of Thai youth : Political Roles in a Democratic System 2) to study Roles and the Political Movement of Thai youth during 1932 - 2020. This article was using historical research method through documentary research. and will present the results by Analytical Description. The results of the study showed that Citizenship awareness of Thai youth varies from time to time. The key factor was the education policy of the Thai government at that period by encourage Thai youth to meet with their ideologies and political goals. Which can be divided into 4 periods: 1) Democracy period 1932-1937 - This is the time when the Thai government wants to raise Thai youth awareness about democracy and freedom. By establishing the relationship between the government, which had a Constitution as the most importance in politic, and the people. 2) Nationalism period 1938-1944 – Thai youth in this period realize that to be a good citizen they must be obey the government and despise the other that does not meet the government definition of “Thai”. 3) The United States of America period 1945-1973 – Thai youth had two mind sets: conservative and progressive in this period. This is a result of the conflict between the Thai youth education policy of the Thai government and the United States which leading to the conflicts between Thai youth and the government. 4) Globalization period 1974-2020 - Thai youth are influenced by globalization in two ways: technology and international organization. Which resulted in an ineffective attempt to instructing Thai youth to be obedience through the education system and raise the awareness of the citizenship that no longer abided to Thai nationalism. And make Awareness of Global Citizenship that out side Thai’s Nationalism and this is the Roles of Thai youth foundation at Expression Awareness of Global Citizenship in Political a Democratic System Continuing until the Present.